Art in China - Clunas, Craig (Oxford history of art, 1997)
Art in China marks a breakthrough in the study of the subject. Drawing on recent innovative scholarship - and on newly-accessible studies in China itself - Craig Clunas surveys the full spectrum of the visual arts in China.